Peran Keluarga Dalam Upaya Pencegahan Adiksi Gawai Anak Usia Dini - Khoirun Nisa (Jurnal Paradigma, 2022)
A gadget is a tool that is easy to find, also known as a gadget and it used in this modern era, commonly used devices such as cellphones (HP), laptops, notebooks and many others, gawais are commonly used by adults, including children. Device addiction is very dangerous for the growth of early childhood so that the role of the family is needed as a prevention of gadget addiction. Interesting to discuss and become the main thing to be more vigilant in giving objects, especially the use of gadgets that are not adjusted to the portion. The approach used is a qualitative descriptive approach. Qualitative data analysis was obtained from observations, interviews, field notes, and documentation studies, by organizing synthesizing data, arranging into patterns, choosing which ones were important and which ones to study, and drawing conclusions.